Climatic design and changing social needs in the tropics: a case study in Kuching, Sarawak - Karol, Elizabeth; Lai, V. (Adver, SUSTDE, 2014)
On the periphery of most urban centres in the tropics, many new houses are being constructed in previously rural areas. However, the design of these houses shows little respect for local climate or local lifestyle, as they are now developer-constructed brick-and-concrete houses on smaller lots rather than community-built housing on large lots. This paper proposes a set of design strategies that acknowledges the particular needs related to climate and changing lifestyle in these tropical zones. Using case study methodology, the design strategies are tested on a prototype for an actual site in Tapah Village on the periphery of Kuching, Sarawak. In order to gauge the thermal performance of the prototype it was thermally simulated. The thermal simulation of the prototype showed that temperatures generally remained within an acceptable range without air-conditioning. An informal workshop was held in Tapah to gauge social acceptance of the design strategies. The prototype demonstrated that specific design strategies, some based on traditional designs, are essential in the tropics in order to minimise the need for air conditioning. These design strategies were acknowledged as important by the local community, although there was concern about the potential increase in the capital cost of such housing.